A Microfluidic Chip-Based MRS Immunosensor for Biomarker Detection via Enzyme-Mediated Nanoparticle Assembly - Yin, Binfeng; Qian, Changcheng; Wang, Songbai; Wan, Xinhua; Zhou, Teng (Frontiers in Chemistry, 2021)
Conventional immunoassay methods have their common defects, such as tedious processing steps and inadequate sensitivity in detecting whole blood. To overcome the above problems, we report a microfluidic chip-based magnetic relaxation switching (MRS) immunosensor via enzyme-mediated nanoparticles to simplify operation and amplify the signal in detecting whole blood samples. In the silver mirror reaction with catalase (CAT) as the catalyst, H2O2 can effectively control the production of Ag NPs. The amount of forming Ag NPs further affects the degree of aggregation of magnetic nanoparticles (MNPS), which gives rise to the changes of transverse relaxation time (T2). Both sample addition and reagent reaction are carried out in the microfluidic chip, thereby saving time and reagent consumption. We also successfully apply the sensor to detect alpha fetoprotein (AFP) in real samples with a satisfied limit of detection (LOD=0.56 ng/mL), which is superior to the conventional ELISA.